Expression and activity levels of chymase in mast cells of burn wound tissues increase during the healing process in a hamster model - DONG, XIANGLIN (Exp Ther Med, 2015)
The present study aimed to investigate the changes in the expression levels and activity of mast cell chymase in the process of burn wound healing in a hamster model of deep second-degree burn. The hamster model was established by exposing a ~3 cm diameter area of bare skin to hot water (75°C) for 0, 6, 8, 10 or 12 sec. Tissue specimens were collected 24 h after burning and histological analysis revealed that hot water contact for 12 sec was required to produce a deep second-degree burn. Quantitative polymerase chain reaction and a radioimmunoassay were used to the determine changes in chymase mRNA expression levels and activity. The mRNA expression levels and activity of chymase were increased in the burn wound tissues when compared with the normal skin. However, no statistically significant differences were observed in mast cell chymase activity amongst the various post-burn stages. Chymase mRNA expression levels peaked at day 1 post-burn, subsequently decreasing at days 3 and 7 post-burn and finally increasing again at day 14 post-burn. In summary, a hamster model of deep second-degree burn can be created by bringing the skin into contact with water at 75°C for 12 sec. Furthermore, the mRNA expression levels and activity of chymase in the burn wound tissues increased when compared with those in normal skin tissues.